Red Blood Cell Abnormalities as the Mirror of SARS-CoV-2 Disease Severity: A Pilot Study - Bouchla, Anthi; Kriebardis, Anastasios G.; Georgatzakou, Hara T.; Fortis, Sotirios P.; Thomopoulos, Thomas P.; Lekkakou, Leoni; Markakis, Konstantinos; Gkotzias, Dimitrios; Panagiotou, Aikaterini; Papageorgiou, Effie G.; Pouliakis, Abraham; Stamoulis, Konstantinos E.; et al. (Frontiers in Physiology, 2022)
Purpose: Unravelling the pathophysiology of COVID-19 disease is of crucial importance for designing treatment. The purpose of this study is to investigate the effects of the disease on erythrocytes (RBCs) and to correlate the findings with disease severity. Materials and Methods: Hospitalized patients (n=36) with COVID-19 and control group of healthy volunteers (n=18) were included in the study. Demographic data, clinical, laboratory and chest Computed Tomography (CT) findings at time of admission were recorded. Laboratory measurements included: Hemoglobin (Ηb), indirect billirubin, LDH, D-Dimers and plasma free hemoglobin (plasma free-Hb). On RBCs were performed: osmotic fragility(MCF), Free-Hb after mechanical stress (Free-Hb-MECH), intracellular RBC concentration of calcium ions (iCa2+), intracellular ROS (iROS), G6PD, intracellular active caspase-3 (RBC-caspase-3), IgG immunoglobulins (RBC-IgGs), which are bound on RBCs’ senescent neo-antigen proteins and RBC surface phosphatidylserine (RBC-PS). Results: The percentage of males was 50% and 66% and the mean age was 65.16±14.24 and 66.33±13.48 years among patients and controls respectively (mean±SD, p=0.78). Upon admission patients’ PO2/FiΟ2 ratio was 305.92±76.75 and distribution of infiltration extend on chest CT was: 0-25% (Ν=19), 25-50%: (Ν=7), 50-75% (Ν=9). Elevated hemolysis markers (LDH and plasma free-Hb) were observed in patients compared to the control group. Patients’ RBCs were more sensitive to mechanical stress, and exhibited significantly elevated apoptotic markers (iCa2+, RBC-PS). Plasma free Hb levels correlated with the extend of pulmonary infiltrates on chest CT in COVID-19 patients. Surprisingly, patients’ RBC-iROS were decreased, a finding possibly related with the increased G6PDH levels in this group, suggesting a possible compensatory mechanism against the virus. This compensatory mechanism seemed to be attenuated as pulmonary infiltrates on chest CT deteriorated. Furthermore, RBC-IgGs correlated with the severity of pulmonary CT imaging features as well as the abnormality of lung function, which are both associated with increased disease severity. Lastly, patients’ D-Dimers correlated with RBC surface phosphatidylserine, implying a possible contribution of the red blood cells in the thrombotic diathesis associated with the SARS-CoV-2 disease. Conclusions: This pilot study suggests that SARS-CoV-2 infection has an effect on red blood cells and there seems to be an association between RBC markers and disease severity in these patients.